2011
DOI: 10.3177/jnsv.57.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Restriction and Intense Physical Training on Estrous Cyclicity and Plasma Leptin Concentrations in Rats

Abstract: SummaryIntense physical training and dietary energy restriction have been associated with consequences such as nutritional amenorrhea. We investigated the effects of intense physical training, food restriction or the combination of both strategies on estrous cyclicity in female rats, and the relationship between leptin ad these effects. Twenty-seven female Wistar rats were distributed into four groups: SF: sedentary, fed ad libitum; SR: sedentary subjected to 50% food restriction (based on the food intake of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
5
5
1
Order By: Relevance
“…The present study showed slightly lower estradiol level among exercise groups and honey supplementation group compared to sedentary group even though the differences were not statistically significant. In a previous study, it was shown that intensive exercise without food restriction was not responsible for significant changes in estradiol concentration level [34]. The discrepancy between the present finding and previous studies may be due to differences in the experimental design.…”
Section: Discussioncontrasting
confidence: 96%
“…The present study showed slightly lower estradiol level among exercise groups and honey supplementation group compared to sedentary group even though the differences were not statistically significant. In a previous study, it was shown that intensive exercise without food restriction was not responsible for significant changes in estradiol concentration level [34]. The discrepancy between the present finding and previous studies may be due to differences in the experimental design.…”
Section: Discussioncontrasting
confidence: 96%
“…Wistar rats, as used in our experiment, might thus be slightly less vulnerable to starvation than the Long-Evans rats. Furthermore, Dos Santos et al showed that female Wistar rats with 50% food restriction for 7 days and access to a treadmill had a reduction in fertile phases but no complete amenorrhoea (Dos Santos et al, 2011). This result fits to our cycle measurements because in our acute starvation model (after seven starvation days), the cycle disturbance was also not complete.…”
Section: Discussionsupporting
confidence: 89%
“…As demonstrated by Dos Santos et al (21), female rats submitted to treadmill exercise and a 50% food restriction led to interruption of estrous cyclicity, as we observed in our study where the physical activity was voluntary. In AN patients, even if amenorrhea was not considered as a criterion in the DSM-5 anymore, disruption of cycles is currently observed in restrictive AN patients (24,42).…”
Section: E252 Chronic Food Restriction and Physical Activitysupporting
confidence: 65%